PENERAPAN PENERAPAN LAPORAN KEUANGAN BERDASARKAN STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO, KECIL DAN MENENGAH (SAK EMKM) - Fandil Fandil; Sarbullah Sarbullah (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2023)
Abstract. Problem that MSME actors generally experience is limited understanding of accounting and ability in accounting. This causes MSMEs to use simple recording by recording cash receipts and disbursements. This study aimed to analyze application of financial statements based on Financial Accounting Standards for Micro, Small and Medium Entities (SEK-EMKM) at UD UMKM. Andalan Jaya. This type of research uses qualitative research. Research design uses qualitative descriptive method. This research was conducted at UD UMKM. Andalan Jaya in Tegal Regency. Kind of data used is primary data. Primary data from this study came from respondents' answers. Data is obtained by conducting interviews, observation, and direct documentation. Data were analyzed using basic accounting in preparing financial statements at UD Andalan Jaya based on 2018 Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) literature. Results show that UD Andalan Jaya does not have financial statements and only has records of sales and purchase transactions, so this is not by guidelines of Financial Accounting Standards for Micro, Small and Medium Entities. This study resulted in UD Andalan Jaya's financial position for December 31, 2020, as follows Assets IDR 1,795,099,224, Liabilities IDR 750,000,000, Capital IDR 1,045,099,224, and Net profit IDR 240,099,224.